(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
This article systematizes the experience of the university outreach project “Ecofeminist menstrual management”, which promotes access to healthy menstrual management with an environmental perspective in the Faculty of Social Sciences (UBA). First, we review pioneering experiences around the promotion of menstrual management in universities and public institutions. Second, we present the perspectives of ecofeminism and critical outreach to address the theory and practice of menstrual management from a multidimensional standpoint. Third, we systematize the experiences of knowledge-sharing dialogues in the intervention devices developed: the workshop, the fair of sustainable products from popular economy cooperatives, the recreational activities and the discussion panel. As a result, the ecofeminist menstrual management project generated great interest beyond the orders of the educational community. From a comprehensive sexual health perspective, the work carried out allows the articulation of the demands of feminist, socio-environmental, popular economy and human rights movements.